Effects of Performance Appraisal on Employee Productivity in Federal Ministry of Education Headquarters Abuja Nigeria - Binta, Mandara; Muhammad, Ibrahim; Ahmed, Zailani; Bazza, Ali Manir; Magaji, Badiya (Asian Journal of Contemporary Education, 2019)
The study examined the effects of Performance Appraisal on Employee Productivity in Federal Ministry of Education Headquarters Abuja. The study used survey research design. The population of the study consists of 1797 employees of Federal Ministry of Education Headquarters Abuja. The sample size of the study was 400 respondents and was determined using Taro Yamane formula. Data for the study was collected using structured questionnaire and analyzed using descriptive and OLS analysis. Results from the findings revealed that the coefficients of appraisal performance and employee feedback had positive and significant effect on employee productivity for the period under study. The coefficients of employee training and employee compensation had positive but insignificant effect on employee productivity for the period under study. The coefficient of multiple determination R2 value of 0.687 percent implied that 68 percent total variation in employee productivity was explained by performance appraisal, employee feedback, employee training and employee compensation. The study recommends that multiple appraisal method should be introduced to further encourage objectivity and eliminate biasedness in the appraisal of workers in the Ministry.